BCA2/Rabring7 Interferes with HIV-1 Proviral Transcription by Enhancing the SUMOylation of IκBα - Colomer-Lluch, Marta (J Virol, 2017)
BCA2/Rabring7 is a BST2 cofactor that promotes the lysosomal degradation of trapped HIV-1 virions but also functions as a BST2-independent anti-HIV factor by targeting Gag for lysosomal degradation. Since many antiviral factors regulate the NF-κB innate signaling pathway, we investigated whether BCA2 is also connected to this proinflammatory cascade. Here, we show for the first time that BCA2 is induced by NF-κB-activating proinflammatory cytokines and that upregulation of BCA2 provides regulatory negative feedback on NF-κB. Specifically, BCA2 serves as an E3 SUMO ligase in the SUMOylation of IκBα, which in turn enhances the sequestration of NF-κB components in the cytoplasm. Since HIV-1 utilizes NF-κB to promote proviral transcription, the BCA2-mediated inhibition of NF-κB significantly decreases the transcriptional activity of HIV-1 (up to 4.4-fold in CD4(+) T cells). Therefore, our findings indicate that BCA2 poses an additional barrier to HIV-1 infection: not only does BCA2 prevent assembly and release of nascent virions, it also significantly restricts HIV-1 transcription by inhibiting the NF-κB pathway. IMPORTANCE Understanding the interactions between HIV-1 and its host cells is highly relevant to the design of new drugs aimed at eliminating HIV-1 from infected individuals. We have previously shown that BCA2, a cofactor of BST2 in the restriction of HIV-1, also prevents virion assembly in a BST2-independent manner. In this study, we found that BCA2 negatively regulates the NF-κB pathway—a signaling cascade necessary for HIV-1 replication and infectivity—which in turn detrimentally affects proviral transcription and virus propagation. Thus, our results indicate that, besides its previously described functions as an antiviral factor, BCA2 poses an additional barrier to HIV-1 replication at the transcriptional level.